2022
DOI: 10.1177/20420188211065655
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative evaluation of the symptoms and quality of life impacts of long-chain fatty acid oxidation disorders

Abstract: Background: Long-chain fatty acid oxidation disorders (LC-FAOD) are a group of rare autosomal-recessive genetic disorders characterized by metabolic deficiencies in which the body is unable to convert long-chain fatty acids into energy. To date, however, there is limited understanding of the patient experience of LC-FAOD. Methods: The symptoms, observable signs, and quality of life (QoL) impacts associated with LC-FAOD were explored via a focus group ( n = 8) and semi-structured interviews ( n = 6) with patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Only few studies have focused on the QoL of patients and caregivers with metabolic disorders, and especially, studies on patients with lcFAODs are scarce. Williams‐Hall et al have recently investigated the QoL impacts associated with lcFAODs via a focus group and semi‐structured interviews with a small number of patients, caregivers, and expert clinicians 11 . In this study, lcFAODs were reported to have a significant impact on various aspects of patients' lives including physical functioning, participation in daily activities, emotional/psychological well‐being, and social functioning 11 .…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Only few studies have focused on the QoL of patients and caregivers with metabolic disorders, and especially, studies on patients with lcFAODs are scarce. Williams‐Hall et al have recently investigated the QoL impacts associated with lcFAODs via a focus group and semi‐structured interviews with a small number of patients, caregivers, and expert clinicians 11 . In this study, lcFAODs were reported to have a significant impact on various aspects of patients' lives including physical functioning, participation in daily activities, emotional/psychological well‐being, and social functioning 11 .…”
Section: Introductionmentioning
confidence: 89%
“…Williams‐Hall et al have recently investigated the QoL impacts associated with lcFAODs via a focus group and semi‐structured interviews with a small number of patients, caregivers, and expert clinicians 11 . In this study, lcFAODs were reported to have a significant impact on various aspects of patients' lives including physical functioning, participation in daily activities, emotional/psychological well‐being, and social functioning 11 . The aims of this study were to (1) describe the challenges of parents and caregivers to care for a child with a lcFAOD and the impact of the disease on different areas of life including the development of coping strategies; (2) explore the differences between mothers and fathers with respect to the different areas of professional, private and family life; and (3) generate an understanding of the unmet needs to further improve the management of lcFAOD.…”
Section: Introductionmentioning
confidence: 99%
“…Although the impact of LC-FAODs on quality of life, work, school, physical activity, and social participation for patients and caregivers has been reported previously, 9 , 11 the impact of LC-FAODs at specific life stages and in the context of the healthcare system has not yet been explored. To gain insights into these issues, we present our perspectives and experiences.…”
Section: Long-chain Fatty Acid Oxidation Disordersmentioning
confidence: 97%
“…For example, some caregivers report via surveys and interviews that they have had to leave their jobs to accommodate the many lifestyle changes required by their children, 9 , 10 such as managing exposure to triggers of acute episodic crises and monitoring diet and weight, periods of fasting and associated energy levels, and signs and symptoms of decompensation. 11 The need to prevent fasting by feeding at regular and frequent intervals can present particular challenges, especially in the early days after diagnosis. 3 These ongoing and significant challenges affect many aspects of patient and caregiver quality of life, including social and physical functioning, interpersonal relationships, work, schooling, emotional and psychological well-being, daily activities, and sleep.…”
Section: Long-chain Fatty Acid Oxidation Disordersmentioning
confidence: 99%
See 1 more Smart Citation